Relationship in dielectric, ferroelectric behaviors and large strain response of BaTiO3-doped (Bi0.4871Na0.4871)La0.0172TiO3 ceramics - Panupong Jaiban (2019)
© 2019 IOP Publishing Ltd. (1-x)(Bi0.4871Na0.4871)La0.0172TiO3-xBaTiO3 ceramics with x = 0.06 and 0.10 were prepared using a solid-state sintering method. The composition x = 0.06 shows coexistence of R3c and P4bm relaxor antiferroelectric phases, while a two-phase mixture of P4bm relaxor antiferroelectric and P4mm is observed for x = 0.10. The P4bm relaxor antiferroelectric nanodomains cause dielectric frequency dispersion in both ceramics. The different characteristics in ferroelectric order of R3c and P4mm phases affect their P-E and S-E hysteresis loops significantly. With the concentration x = 0.10, large piezoelectric coefficient can be pronounced. The result here suggests that BNLT properties may be tunable by BT doping, which could be applied with much potential use with lead-free actuator applications.